POLA ASUH ORANG TUA YANG BEKERJA SEBAGAI PETANI SAWAH DI KELURAHAN PULAU KECAMATAN BANGKINANG KABUPATEN KAMPAR - Ela Soleha; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the more dominant parenting between authoritarian, democratic, and permissive applied to parents who work as rice farmers in Kelurahan Pulau Kecamatan Bangkinang Kabupaten Kampar. This study has 3 indicators, namely (1) authoritarian parenting (authoritarian), (2) authoritative parenting (democracy), and (3) permissive parenting (laissez-faire). The sample in this study used a simple random sampling technique (simple random sampling). The population in this study were 59 people. So the sample of this study was 37 people and 20 people were trial samples. The data collection technique in this study was a questionnaire technique. The data of this research are systematic, planned and clearly arranged data from the beginning to the making of the research design. Validity test was conducted on 20 parents (mothers), with a critical r value of 0.444. Of the 55 statement items that were tested, 4 statements were invalid and 51 were valid. So that 51 legitimate questionnaire items were used for research. Based on the results of the analysis that has been carried out, it can be concluded that the results of this study note that parenting (mother) who works as a rice farmer in Kelurahan Pulau Kecamatan Bangkinang Kampar Regency is classified as good. Seen from an authoritarian parenting more dominant, compared to democratic parenting and permissive parenting although both are applied.Key Words: Reading Interest, Factors That Affects The Low Reading Interest